Effects of bacteriophages and peroxyacetic acid applications on beef contaminated with Salmonella during different grinding stages. (March 2021) - Shebs-Maurine, E.L.; Giotto, F.M.; Laidler, S.T.; de Mello, A.S.
Abstract: Research has suggested that the incidence of Salmonella in ground beef may be associated with contaminated lymph nodes that are not removed from trimmings destined for grinding. In this study, we tested the application of bacteriophages and peroxyacetic acid solutions on trimmings and on coarse and fine ground beef to simulate different scenarios of contamination. Overall, peroxyacetic acid applications did not reduce Salmonella loads on ground beef when applied on trimmings or at any stage of grinding. When applied on contaminated trim, bacteriophage solutions at 1 × 10 8 PFU/g and 1 × 10 9 PFU/g reduced more than 1 log cfu/g of Salmonella . When applied directly on contaminated coarse or fine ground beef, bacteriophage solutions at 1 × 10 9 PFU/g reduced approximately 1.6 log cfu/g. Results of this study suggest that bacteriophage applications on contaminated, comminuted beef may be used as an aid to decrease Salmonella loads. Highlights: Salmonella contamination in ground beef was recently associated with ground contaminated lymph nodes. Peroxyacetic acid does not significantly reduce Salmonella in ground beef. Application of bacteriophages either on trimmings or directly on ground beef reduce Salmonella load. Higher concentrations of bacteriophages provided optimal reduction when applied on comminuted beef.